Pemanfaatan Media Sosial Sebagai Sarana Promosi Budaya Lokal Oleh Remaja Melalui Pelatihan Branding Digital di Kawasan Wisata - Adha, Muhammad Mona; Utami, Rahma Kurnia Sri; Istiawati, Novia Fitri; Wahyudi, Apri (CV. Kurnia Grup, 2025)
The rapid development of digital technology in the Industrial Revolution 4.0 era has transformed social media from a communication tool into a strategic medium for cultural promotion. However, many youths still use social media passively without understanding its potential to strengthen local culture and tourism. This issue became the basis for implementing a community service program at SMP Negeri 44 Bandar Lampung, aiming to improve students’ digital literacy and skills in using social media as a platform for promoting local culture through digital branding training. The activity applied a participatory training method through workshops, group discussions, and mentoring. The results showed that students’ abilities in creating creative content such as videos, posters, and cultural narratives increased significantly. These works were published on the school’s social media account as part of local culture promotion efforts. This program successfully fostered cultural awareness and creativity among students, serving as a model for youth empowerment through digital-based cultural preservation.